Modeling study of combustion and pollutant formation in HCCI engine operating on hydrogen rich fuel blends. (9th February 2016) - Kozlov, V.E.; Chechet, I.V.; Matveev, S.G.; Titova, N.S.; Starik, A.M.
Abstract: Comprehensive analysis of combustion and emission characteristics of HCCI engine operating on alternative fuels, including methane, syngas, methane/hydrogen and methane/syngas blends is conducted on the basis of CFD simulation with the use of detailed reaction mechanism. It is shown that the replacement of methane to methane/hydrogen blend with 50% H2 volume content makes it possible to increase the output energy during HCCI combustion and simultaneously to reduce the NO and CO emissions. The use of methane/syngas blend as a fuel also leads to an improvement of HCCI performance and to reducing the pollutant emissions, including the emission of CO2 . Highlights: 2D CFD simulation of combustion and emission characteristics of HCCI engine is conducted. CH4, syngas, CH4 /H2 and CH4 /syngas blends were considered as a fuel. Replacement of CH4 by CH4 /H2 blend increases output energy and decreases substantially CO emission. The usage of CH4 /syngas blend improves HCCI performance and reduces the pollutant emissions. Addition of a certain amount of H2 or syngas to CH4 can decrease NO emission.